Islamic work ethic: where are we now? The map of Islamic work ethic - Jaya Addin Linando (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
Islamic Work Ethic (IWE) is a concept coined by Ali (1988) thirty years ago. IWE is interesting as Moslem population all around the world keeps growing and Moslem should pay attention toward the ethical conduct in the workplace as in Islam, working is an ibadah (a prayer or a virtue). This article aims to compile the researches with IWE topic, especially those show the relation between IWE and other variables in a sequence of antecedents and consequences. The final result of this article is an ‘IWE Map’ that might help researchers and practitioners to see the big picture of IWE, at least up to today. The dimensions and statements to characterize IWE is also compiled and shown in this article.